2020
DOI: 10.3390/su12219233
|View full text |Cite
|
Sign up to set email alerts
|

Peer Assessment in Physical Education: A Systematic Review of the Last Five Years

Abstract: Purpose: A systematic review of the use of peer assessment in Physical Education in the last five years (2016–2020). Method: Four databases were used to select those articles that included information on peer assessment in Physical Education in the different educational stages. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including the PICO (participants, intervention, comparators, and outcomes) strategy, after the exclusion criteria, 13 articles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 74 publications
0
11
1
3
Order By: Relevance
“…The absence of studies on self-assessment in physical education in the primary stage was conspicuous in this systematic review. These results do not coincide with the recent review conducted by Bores-García, Hortigüela-Alcalá González-Calvo, and Barba-Martín [42] on coassessment in physical education. In that study, the primary stage was represented by coassessment formative assessment strategies.…”
Section: Educational Stagecontrasting
confidence: 99%
“…The absence of studies on self-assessment in physical education in the primary stage was conspicuous in this systematic review. These results do not coincide with the recent review conducted by Bores-García, Hortigüela-Alcalá González-Calvo, and Barba-Martín [42] on coassessment in physical education. In that study, the primary stage was represented by coassessment formative assessment strategies.…”
Section: Educational Stagecontrasting
confidence: 99%
“…This is because the developed teamwork skill instrument is not accompanied by a detailed rubric. Students should utilize a checklist or some sort of grading rubric to assess each other or as a group to illustrate what is being done, how acceptable it is, and what needs further work (Bores-García et al, 2020). Overall, the results of the three assessments showed that The STEM project-based learning is effectively able to train students' teamwork skills.…”
Section: Join the Teammentioning
confidence: 99%
“…La evaluación entre pares o coevaluación favorece la autorregulación y la autonomía, permite que el estudiantado se involucre más en su aprendizaje, adquiera mayores responsabilidades e incremente su motivación (Bores-García et al, 2020;Panadero & Alonso-Tapia, 2013).…”
Section: Actoresunclassified